Attosecond spectroscopy reveals alignment dependent core-hole dynamics in the ICl molecule - Marroux, Hugo J. B.; Fidler, Ashley P.; Ghosh, Aryya; Kobayashi, Yuki; Gokhberg, Kirill; Kuleff, Alexander I.; Leone, Stephen R.; Neumark, Daniel M. (Nature Communications, 2020)
The removal of electrons located in the core shells of molecules creates transient states that live between a few femtoseconds to attoseconds. Owing to these short lifetimes, time-resolved studies of these states are challenging and complex molecular dynamics driven solely by electronic correlation are difficult to observe. Here, we obtain few-femtosecond core-excited state lifetimes of iodine monochloride by using attosecond transient absorption on iodine 4d−16p transitions around 55 eV. Core-level ligand field splitting allows direct access of excited states aligned along and perpendicular to the ICl molecular axis. Lifetimes of 3.5 ± 0.4 fs and 4.3 ± 0.4 fs are obtained for core-hole states parallel to the bond and 6.5 ± 0.6 fs and 6.9 ± 0.6 fs for perpendicular states, while nuclear motion is essentially frozen on this timescale. Theory shows that the dramatic decrease of lifetime for core-vacancies parallel to the covalent bond is a manifestation of non-local interactions with the neighboring Cl atom of ICl.
Gesehen am 21.01.2021